Maintenance Management Jacro 175 Drill Rig for Coal Exploration Work Using the Reliability Centered Maintenance (RCM) Method in PT Inti Bangun Mulya - Jefli, Polii Renaldy; Sitania, Farida Djumiati (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2026)
PT. Inti Bangun Mulya was established in 2019 and is a company engaged in consulting and contracting services in the mining sector, including mapping, topography, mineral exploration, mineral modeling, mine design, mine economic evaluation, and resource and reserve calculation. This research aims to determine the critical components and to identify an effective and efficient maintenance schedule for the Jacro 175 Rig components. In determining critical components and creating a maintenance schedule, the researchers used Reliability Centered Maintenance (RCM) with the application of an appropriate and systematic maintenance system. This research uses a research method employing RCM and Failure Mode and Effect Analysis (FMEA). Data collection techniques include observation, interviews, and questionnaires. The initial steps taken by the author were to identify functions and failures, analyze system failures occurring in the Yanmar TF 105 machine, analyze critical level criteria, analyze FMEA, determine appropriate task selection, calculate the reliability value of critical components, and provide repair proposals in the form of an efficient maintenance schedule for critical components. The results of this study indicate that PT. Inti Bangun Mulya is known to implement a maintenance management system using a corrective maintenance system that is less effective and efficient for application to all components. Therefore, the author proposes an improvement in the form of a maintenance schedule for critical components.